Exploring the Role of GMMA Components in the Immunogenicity of a 4-Valent Vaccine against Shigella - Mancini,F; Alfini,R; Caradonna,V; Monaci,V; Carducci,M; Gasperini,G; Piccioli,D; Biagini,M; Giannelli,C; Rossi,O; Pizza,M; Micoli,F (International Journal of Molecular Sciences, 2023)
Shigellosis is the leading cause of diarrheal disease, especially in children of low- and middle-income countries, and is often associated with anti-microbial resistance. Currently, there are no licensed vaccines widely available against Shigella, but several candidates based on the O-antigen (OAg) portion of lipopolysaccharides are in development. We have proposed Generalized Modules for Membrane Antigens (GMMA) as an innovative delivery system for OAg, and a quadrivalent vaccine candidate containing GMMA from S. sonnei and three prevalent S. flexneri serotypes (1b, 2a and 3a) is moving to a phase II clinical trial, with the aim to elicit broad protection against Shigella. GMMA are able to induce anti-OAg-specific functional IgG responses in animal models and healthy adults. We have previously demonstrated that antibodies against protein antigens are also generated upon immunization with S. sonnei GMMA. In this work, we show that a quadrivalent Shigella GMMA-based vaccine is able to promote a humoral response against OAg and proteins of all GMMA types contained in the investigational vaccine. Proteins contained in GMMA provide T cell help as GMMA elicit a stronger anti-OAg IgG response in wild type than in T cell-deficient mice. Additionally, we observed that only the trigger of Toll-like Receptor (TLR) 4 and not of TLR2 contributed to GMMA immunogenicity. In conclusion, when tested in mice, GMMA of a quadrivalent Shigella vaccine candidate combine both adjuvant and carrier activities which allow an increase in the low immunogenic properties of carbohydrate antigens.